Psychosocial Stress, Cortisol Levels, and Maintenance of Vaginal Health - Amabebe, Emmanuel; Anumba, Dilly O. C. (Frontiers in Endocrinology, 2018)
Stress stimuli are ubiquitous and women do not enjoy any exemptions. The physiologic “fight-or-flight” response may be deleterious to the female lower genital tract microbiome if the stress stimuli persist for longer than necessary. Persistent exposure to psychosocial stress and stimulation of the hypothalamic-pituitary-adrenal (HPA) and sympathetic-adrenal-medullary (SAM) axes, and associated hormones are risk factors for several infections including genitourinary tract infections. Though this could be due to a dysregulated immune response, a cortisol-induced inhibition of vaginal glycogen deposition may be involved especially in the instance of vaginal infection. The estrogen-related increased vaginal glycogen and epithelial maturation are required for the maintenance of a healthy vaginal ecosystem (eubiosis). The ability of cortisol to disrupt this process as indicated in animal models is important in the pathogenesis of vaginal dysbiosis and the subsequent development of infection and inflammation. This phenomenon may be more crucial in pregnancy where a healthy Lactobacillus-dominated vaginal microbiota is sacrosanct, and there is local production of more corticotropin-releasing hormone (CRH) from the decidua, fetal membranes and placenta. To highlight the relationship between the stress hormone cortisol and the vaginal microbiomial architecture and function, the potential role of cortisol in the maintenance of vaginal health is examined.